Pengaruh Ukuran Perusahaan Growth Opportunity Dan Profitabilitas Terhadap Nilai Perusahaan (Studi Empiris Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2012-2015) - Nulatsih, Henny Tri; , Dr. Syamsudin, M.M (2017)
This research aims to analyze the effect of firm size, Growth Opportunityand profitability Of the company are measured using a price book value, on manufacture companies listed on the Indonesia stock exchange in 2012-2015. The population used in this study are manufacture companies listed on the Indonesia stock exchange in 2012-2015. Sampling method sampling purposive manner in accordance with the criteria specified. The number of samples collected as many as 30 companies. Research data is secondary data obtained from the Indonesian Capital Market Directory (ICMD) in 2012-2014 and the data provided on the website of the indonesia stock exchange (www.idx.go.id) by 2015. Data that has been collected is analyzed by using the data analysis done first before doing the classic assumption test hypothesis testing. Hypothesis testing in this study using multiple linear regression analysis with t test, f test and a test of the determination of the coefficients using the SPSS program.The results showed that simultaneously throughout the independent variable firm size, growth opportunity and profitability in this research the positive and significant effect against the value of the company's manufacture companies listed on the Indonesia stock exchange in 2012-2015. Companies need to pay attention to the firm size, growth opportunity and profitability that when increasing the third variable occurs then investors will be attracted to the company by investing capital.